(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The high yield electrophilic substitution procedure for the synthesis of bis indolyl methanes at room temperature has been carried out effectively by using a novel metal supported organo catalyst. The advantages of this method include a simple conditions, great yields, less work-up, an environmentally friendly process and reusable solid catalyst. Several bis indolyl methanes were synthesised and confirmed by IR, H1 and 13C NMR techniques. The Catalyst shortens the Indole Electrophilic Substitution reaction time.